Kur'an-ı Kerim'de iftirak kavramı - MOHAMMED, JUNAID JABAR (Fırat Üniveristesi, 2020)
Ayrılık ayetlerinin büyük bir misyonu var, Müslümanların bunu öğrenmeleri lazımdır çünkü bunlar Dünya ve ahiret saadeti ile alakalıdır ne zaman ki ayrılmayı öğrendiğimizde ve dinde ayrılmanın Müslümanlar için çok zararları olduğunu öğrendiğimizde o zararlar dünyada bir zillet ve gücün zaifliği kıyamette de ayrılanlar için bir azap ve helak olduğunu gösterir. O zaman bundan Korunmamız lazım ayrılmanın çok sebepleri vardır. Müslümanlar için dinde ayrılmaları caiz değildir çünkü bu büyük günahlardandır ve burda ayrılmadan korunmanın yolları vardır ve Müslümanların bu yola sarılmaları lazım ki bu büyük hastalıktan kurtulsunlar. Müslüman topluluğunun tanıtımının bu dünyada ve ahirette birçok faydası vardır. Anahtar kelimeler: Ayrılık, Müslümanlar, Çoktanrıcılar, Fark, Işkence

The verses of separation have a big task, Muslims must know this importance because it relates to happiness in this world and the hereafter, and if we know the separation and know that the occurrence of separation in religion has many damages to the nominees which is humiliation and weak power in the world and torment and destruction for those who separate on the Day of Resurrection at this time we avoid from it And there are many reasons for separation, and it is not permissible for Muslims to separate in religion because it is a major sin. Also, there are ways to prevent separation that Muslims must adhere to to escape from this great disease, and adherence to the Muslim community has many benefits in this world and the hereafter. Key words: separation, Muslims, polytheists, difference, torture
Concept of slander in the Quran - Mefhumu'l-iftirak fi'l-Kur'anı'l-Kerim
Keywords: Din